Tindak Tutur Ilokusi dan Fungsinya dalam Wacana Iklan Lingkungan Hidup di Media Sosial - A. Pekuwali, Dian Sari (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
This research intends to analyze the form and function of the speech discourse of the environment found in social media. This type of research is a qualitative study. Technique of collecting data use method of note and note technique, advanced image technique. Data analysis techniques use heuristic methods. The technique of presenting the analysis result is informal method. Data analysis techniques use heuristic methods. The technique of presenting the analysis result is informal method. The results of this research (1) There are 2 types of act of speech of ilokusi that is; assertive speech and direct acting. Assertive action include; (a) say, (b) notify, (c) assert. Directive actions include; (a) rule, (b) prohibit, (c) require, (d) invoke, (e) suggest, (f) to remember. The kind of commissive, expressive and declarative speech acts not found in this study. (2) There are 4 functions, namely competitive, fun, cooperative, conflicting function. Competitive functions include; (a) order, (b) request. Fun functions include; (a) offer, (b) invite, (c) welcome. The cooperative function includes; (a) announce, (b) instruct. The conflicting functions include; (a) threatening, (b) condemning, (c) reprimand.